Case Report: 18F-FDG PET/CT revealed diffuse pancreatic metastasis in paranasal sinuses rhabdomyosarcoma after treatment improvement - Hu, Xianwen; Duan, Haojun; Zhao, Ying; Wang, Yongpeng; Pan, Dongfeng (Frontiers in Medicine, 2025)
Metastasis of rhabdomyosarcoma (RMS) from primary paranasal sinuses to the pancreas is rare. Herein, we present a rare case of diffuse pancreatic metastasis in a 44-year-old man. He was diagnosed with sinus RMS 1 year ago and the lesion disappeared after systematic treatment. The patient came to our hospital in November 2022 due to abdominal pain. Abdominal ultrasound showed diffuse enlargement of the pancreas, with enlarged lymph nodes visible around the pancreas and retroperitoneum. He then underwent positron emission tomography/computed tomography (PET/CT) imaging and the results showed that the pancreas had diffusely increased fluorine-18 fluorodeoxyglucose (18F-FDG) uptake, and the surrounding pancreas and retroperitoneal lymph nodes also had increased 18F-FDG uptake, suggesting a possibility of malignant tumor. Ultimately, a pancreatic puncture biopsy confirmed RMS with pancreatic and abdominal lymph nodes metastasis. Our case suggests that although diffuse metastatic tumors of the pancreas are relatively rare, which should be considered as one of the differential diagnoses for diffuse pancreatic hypermetabolic lesions on PET/CT imaging.